Case Report: Coronary vasospasm precipitating STEMI and polymorphic ventricular tachycardia—a case of cardiotoxicity from 5-FU based chemotherapy in a 41-year-old woman - Hasnie, Ammar; Neace, Zachary; Ellison, Kristin; Hesselson, Aaron; Ayoub, Karam; Al-Yafi, Mohammed; Arbune, Amit (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIntravenous 5-fluorouracil (5-FU), in combination with oxaliplatin and folinic acid, makes up a chemotherapy regimen commonly referred to as FOLFOX. It is well-established for its efficacy in patients with advanced colorectal cancer; however, the benefits are accompanied by potential side effects that warrant careful consideration. Common toxicities can range from nausea and vomiting to neuropathy. Cardiotoxicities related to FOLFOX and fluoropyrimidines in general are extremely rare but can easily be fatal.Case presentationA 41-year-old woman who was recently diagnosed with stage IIIc colorectal cancer after she underwent a subtotal colectomy was admitted to the Oncology clinic for further treatment. Given her excellent performance status and lack of comorbidities, she was started on adjuvant FOLFOX therapy. Three days after her first dose, she presented to the emergency room with several episodes of self-limited substernal chest pain. An electrocardiogram was performed, which showed ST-segment elevation concerning for acute myocardial infarction. She was taken emergently for a coronary angiogram, which revealed no evidence of obstructive coronary artery disease or spontaneous coronary artery dissection. Her presentation was most consistent with coronary vasospasm secondary to her recently started chemotherapy regimen. She was monitored in the cardiac critical care unit; the next day, she developed a breakthrough chest pain and subsequently developed polymorphic ventricular tachycardia with loss of consciousness. It was found that she had suffered a breakthrough coronary vasospasm precipitating a life-threatening arrhythmia. She was started on calcium channel blockers and nitrates with the aim of preventing further episodes of her hypersensitivity-induced vasospasm, and she was eventually successfully rechallenged with a Nordic FLOX bolus-based regimen.ConclusionsIn an unusual fashion, our patient developed ST-segment elevation myocardial infarction (STEMI) caused by coronary vasospasm, followed by delayed polymorphic ventricular tachycardia approximately 24 h later. This dual-phase presentation and subsequent successful rechallenge with bolus-based 5-FU chemotherapy have not been previously reported.